A Debreceni Egyetem Műszaki Karának fél évszázada - Bíró, Noémi; Szűcs, Edit (Gerundium, 2015)
50 YEARS OF THE TECHNOLOGY FACULTY OF THE UNIVERSITY OF DEBRECEN. he study reviews the higher education background of the technology education from 1965–2000 in relation to its teaching and organizational history. It describes the anniversary ceremony of the Technology Faculty organized in May 2015. hrough a selection of the most important statements at this ceremony, the writing shows the reults of the Faculty in the past 15 years.